Spike Gene Target Failure Among RT-PCR Positive SARS-CoV-2 Samples in Dhaka City During Early Variant Waves: Spike Gene Target Failure among RT-PCR positive SARS-CoV-2 (Journal of Preventive and Social Medicine, 2026)
Background: Real time RT-PCR is a widely used method for detecting SARS-CoV-2, the causative agent of COVID-19 infection. A phenomenon termed ‘spike gene target failure’ (SGTF) has been reported in certain SARS-CoV-2 lineages, in which there is failure to detect the spike (S) gene target in samples that are positive for other RT-PCR targets, which occurs due to a deletion of six nucleotides in the spike gene (69-70del). The SGTF trait has been validated as a reliable surrogate marker for presence of 69-70del in the viral genome. We retrospectively determined the prevalence of SGTF trait among COVID-19 positive samples in Dhaka city.Methods: The study was conducted in the department of Virology at National Institute of Laboratory Medicine and Referral Center (NILMRC), Dhaka between November 2020 and June 2021. A total of 5,259 nasopharyngeal and oropharyngeal swab samples that tested positive for SARS-CoV-2 with TaqPath COVID-19 Combo PCR kit, were screened for the SGTF marker. SGTF was defined as the non-detection of S-gene-target in samples that were positive for both N and ORF1ab targets with Ct values ≤30.Results: Among 5,259 PCR-positive samples, 144 (2.74%; 95% CI: 2.30%, 3.20%)) showed SGTF trait in our study. The peak SGTF detection rate was observed in February 2021 (10.77%; p